Analysis of Biodiesel Cotton Seed Oil on Diesel Engine Performance - Semin; Adhi Iswantoro; Gage Cendekiaji Hadi (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2018)
The world crisis of fossil fuel availability encourages the development to explore alternative energy which is possible to replace of fossil fuel. The use of biodiesel by using vegetable oil and animal fats is strived to the maximum extent possible, in order to maintain its sustainability. Cotton Seed oil (Ceiba Pentandra) is one alternative that can be used as a substitution fuel. There are four advantages of using Cotton Seed oil as a substitute fuel which are: produce a low level of pollutant, guaranteed availability, can be used for diesel engines with less or no modification and in certain mixes can increase engine lubrication that should increase engine life. The research was conducted through performance test of YANMAR TF85-MH diesel engine using Cotton Seed oil biodiesel with mixture of B30, B20 which has been compared with using diesel oil. From the results of experiment, it showed that the use of Cotton Seed oil has been increase performance than diesel fuel. The addition of biodiesel Cotton Seed oil percentage into the fuel provide greater power but it provides the higher fuel consumption.